Lack of association between ACE gene insertion/deletion polymorphism and elite artistic gymnastic performance of Italian gymnasts - Massidda, M.; Calo, C. M. (European Journal of Sport Science, 2011)
The angiotensin converting enzyme (ACE) polymorphism is the most studied genetic marker in the field of human performance. There is a continuing debate in the literature regarding the possible association of ACE genotypes and elite athletic status. In fact, despite recent studies having identified no significant associations in athletes from mixed sporting disciplines, other researchers suggest that the insertion (I) variant may be associated with elite endurance performance, and the deletion (D) variant can be over-represented among elite sprinters. The purpose of the present study was to determine, for the first time, the association between the ACE genotypes and sprint athlete status among elite Italian gymnasts. To test this hypothesis, we assessed 33 elite Italian gymnasts (17 males, 16 females) and a control group of 53 (31 males, 22 females) unrelated sedentary individuals. DNA was extracted from each participant using a buccal swab and the ACE I/D polymorphism was determined using PCR while different amplified fragments were detected by electrophoresis using agarose gel and ethidium bromide staining. The ACE genotypes and allele frequencies among gymnasts (DD, ID, II=0.39, 0.48, 0.12, respectively; D allele=0.64) were not significantly different from those of Italian sedentary controls (DD, ID, II=0.39, 0.45, 0.15, respectively; D allele=0.62). However, the frequencies of our control group were similar to those observed in a sample of Italian sedentary individuals, and different to those of the general Caucasian population reported by other authors. Furthermore, the frequencies of our control group did not differ from those reported in other association studies involving elite sprint athletes. Our results suggest a lack of association between the ACE I/D polymorphism and elite gymnastics performance in Italians.